Comperative analasys of JavaScript runtime environments - Kalman, Konrad; Miłosz, Marek (Journal of Computer Sciences Institute, 2025)
This article presents a comparative analysis of two JavaScript runtime environments: Node.js, the industry leader since 2009, and Bun, a newer and promising alternative introduced in 2022. The study evaluates their performance in two distinct experimental scenarios: handling HTTP requests and executing a computationally intensive algorithm for calculating Fibonacci numbers. These scenarios allow for the assessment of both I/O-bound and CPU-bound workloads. Benchmarking tools were used to measure the most important metrics, including total request handling time, average latency, and peak memory usage. By analyzing architectural differences and runtime optimizations, the article highlights the advantages and trade-offs of both environments. The findings offer developers valuable insights for selecting an appropriate platform for high-performance and scalable server-side applications, and contribute to the ongoing discussion on the evolution of JavaScript runtimes.